2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610577
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception rehabilitation training system for stroke patients using virtual reality technology

Abstract: We investigated a virtual reality (VR) proprioceptive rehabilitation system that could manipulate the visual feedback of upper-limb during training and could do training by relying on proprioception feedback only. Virtual environments were designed in order to switch visual feedback on/off during upper-limb training. Two types of VR training tasks were designed for evaluating the effect of the proprioception focused training compared to the training with visual feedback. In order to evaluate the developed prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…To improve proprioception, sensorimotor training programs have been suggested to facilitate joint position sense and dynamic joint stability using rhythmic active motion, angle repositioning, and standing on an air cushion with support to stimulate muscular co-activation [11]. Kim et al investigated a new type of rehabilitation system to train proprioception of stroke patients using virtual reality technology [12]. The system requires that patients move their arm to the target position relying on proprioception feedback only.…”
Section: Sensorimotor Functionsmentioning
confidence: 99%
“…To improve proprioception, sensorimotor training programs have been suggested to facilitate joint position sense and dynamic joint stability using rhythmic active motion, angle repositioning, and standing on an air cushion with support to stimulate muscular co-activation [11]. Kim et al investigated a new type of rehabilitation system to train proprioception of stroke patients using virtual reality technology [12]. The system requires that patients move their arm to the target position relying on proprioception feedback only.…”
Section: Sensorimotor Functionsmentioning
confidence: 99%
“…In these studies, which included both uni-and bi-manual paradigms, the level of force assistance was adjusted based on individuals' motor function and their performance, and it was shown that such a protocol could improve the sense of limb position and movement, but retainment of gained benefits for stroke individuals might also be affected by the level of stroke-related impairment [10]. Proprioceptive training through delayed visual feedback in a virtual reality platform was addressed in [19,20]. In this regard, individuals with stroke were asked to transfer objects in a virtual environment to a predefined target without visual feedback of the location of their hands.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the aforementioned studies focused on proprioceptive training through specifically administering a set of tasks for improving sensorimotor function [11]. Moreover, protocols implemented for assessing and improving position sense in upper limbs considered two-dimensional space and administered isolated movements mostly in the transverse plane [10,[12][13][14][15][16][17][18][19][20] and sagittal plane [22][23][24][25]. As a large number of activities of daily living require moving the upper-limbs in three-dimensional (3D) trajectories [26], there is a need for rehabilitation protocols that require participants to practice movements in 3D space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies are strongly associated with proprioception or the ability to sense the position of the body in time and space [31]. Stroke patients usually depend on visual function when they move part of their body for example, during eating and walking because they have impaired proprioception [32,33]. Tasks should have a clear guidance path so that the subject understands easily what they should do.…”
Section: Main Issues To Discussmentioning
confidence: 99%